Growth of Different Sizes of Bulbil Iles-iles (Amorphophallus muelleri Blume) on Several Planting Media Types - Sumarwoto Sumarwoto; Maryana Maryana (Jurnal Ilmu Kehutanan)
Iles-iles or porang produces various sizes of bulbils, and farmers usually use only large ones. In this study, all sizes of bulbil: small, medium and large were grown on several planting media types. The purpose of this experiment is to obtain the best bulbil growth and the most suitable media for the initial growth of plant material in the form of bulbil. In addition, this study aims to test the interaction of both factors, bulbil size and type of planting media on bulbils produced. The experiment was done in the Faculty of Agriculture UPN "Veteran" Yogyakarta experimental field in Condongcatur, at 115 m asl, at the beginning of rainy season of 2010/2011. The experiment was done with two-factors and three replications constructed in Randomized Block Design. The first factor was the size of the bulbil (U) consisting of three levels: U1 small (± 1.5 gram), U2 medium (± 5 gram), and U3 large (± 10 gram). The second factor is the type of planting media which consists of three levels: M1 (soil + litter), M2 (soil + cow manure), and M3 (soil + chicken manure).The results showed that medium size and large size bulbil are good to be used as seeds, while the small one can be used as seed only if it has been maintained in special treatment. M3 planting medium (soil + chicken manure) has given the best result compared to the other 2 treatments. Results of interaction test showed that there were interactions of both factors on some parameters including diameter leaf canopy, pseudo-stem diameter, root diameter and fresh weight of bulb.